Returning to Spiritual Sense: Cruciform Power and Queer Identities in Analytic Theology - David A. C. Bennett (Religions, 2023)
In recent theological scholarship, there has been a wave of interest in the tradition of spiritual sense and marginal social identities within analytic and philosophical theology. In this article, I explore the theologies of spiritual sense in analytic theology (AT) to highlight part of the reason for the predominance of cisgender heterosexual voices in the field. Many feminist voices in AT express a common concern for a lack of integration between the mind, the body, and spiritual sense, which has enshrined the post-enlightenment cisgender heterosexual ‘man of reason’. Through an exploration of these feminist voices (Sarah Coakley and Michelle Panchuk), I argue that the field does not simply need more diverse voices but also voices of spiritual sense that undo a straight cisgender elitism. This elitism has kept the field from widely examining the anthropological questions of sexuality and gender, ethics, and theodicean dilemmas of desire and faith. By opening analytic philosophical approaches to spiritual sense, the field releases noetic control that has two consequential outcomes. Firstly, the field revalorizes pneumatology and ethics. Secondly, as a consequence of this, the field can see those who were previously unseen and heard, and, therefore, AT can develop into a sensing and thinking discipline capable of perceiving the queer or other in its midst. Spiritual sense and its priority for bodily and cruciform realities of suffering and desire can move the field from homogeneity to embracing the diverse ethical concerns of sexuality, gender, and race, and subaltern or queer subjectivities which are yet to be represented well in its midst. Using a distinctly neo-Augustinian approach, I argue that Augustine’s philosophy of the amor dei, with its emphasis on analytic clarity and inner spiritual sense, can redeem the eyes of AT’s heart.